Predicting choice of Theme-park destinations in India - Malhotra, Gunjan (ITB Journal Publisher, LPPM ITB, 2017)
Purpose: In this paper we attempt to understand the factors that provides satisfaction to the visitors of theme-park destinations and to predict visitors’ intent to re-visit the theme park destinations in India. Methodology: We have applied factor analysis to understand the attributes that attract visitors to re-visit theme parks and logistic regression techniques to predict if the visitor’s intent to re-visit theme-park destinations on a regular basis.Findings: The results suggest that major factors that visitors consider while confirming re-visit to theme parks in India include lifestyle, historical and leisure. Moreover, tourists visiting such theme parks are always interested in new, innovative and creative ideas to attract and plan their visits on a regular basis. The visitors prefer to experience and feel India mainly listening to regional music and enriching its cultural and historical importance.Originality: This will promote Indian tourism industry by motivating managers to bring up new, creative and innovative ideas to attract more visitors in theme-parks. Business managers may expand their existing business plans in Indian tourism industry.